2008
DOI: 10.1002/j.1551-8833.2008.tb09653.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: Charting a water course in an uncertain future

Abstract: The planet is warming, and many scientists agree that the rise in temperature is human‐made. However, science has not developed a model to predict the effects of increasing temperatures. Still, water utilities can and must plan for the uncertainties of climate change and its effects on water supplies and operations. The findings of a comprehensive case study, conducted by the East Bay Municipal Utility District in California on strategies to mitigate and adapt to climate changes, are presented in this article.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Estimates indicate that approximately 90% of the electricity purchased by U.S. water utilities, US$10 billion per year, is required for pumping water through the various stages of extraction, treatment, and final distribution to consumers [Bunn, 2011;Skeens et al, 2009]. Further, the energy use in water utilities, with the exclusion of energy use for water heating by residential and commercial users, contributes significantly to an increasing carbon footprint with an estimated 45 million tons of greenhouse gas (GHGs) emitted annually in U.S. into the atmosphere [Griffiths-Sattenspiel and Wilson, 2009;Wallis et al, 2008;Kanakoudis, 2014].…”
Section: Introductionmentioning
confidence: 98%
“…Estimates indicate that approximately 90% of the electricity purchased by U.S. water utilities, US$10 billion per year, is required for pumping water through the various stages of extraction, treatment, and final distribution to consumers [Bunn, 2011;Skeens et al, 2009]. Further, the energy use in water utilities, with the exclusion of energy use for water heating by residential and commercial users, contributes significantly to an increasing carbon footprint with an estimated 45 million tons of greenhouse gas (GHGs) emitted annually in U.S. into the atmosphere [Griffiths-Sattenspiel and Wilson, 2009;Wallis et al, 2008;Kanakoudis, 2014].…”
Section: Introductionmentioning
confidence: 98%
“…Water utilities are an indirect source of carbon emissions because of the use of energy in distribution systems (Wallis et al, 2008). These systems have generally been designed and operated to consistently supply water in sufficient quantity, at appropriate pressure, and of acceptable quality as economically as possible.…”
Section: Resultsmentioning
confidence: 99%
“…American Water, the largest investor‐owned water and wastewater company in the United States, reported that 97% of its electricity consumption and 90% of its greenhouse gas emissions are the products of the water delivery process (Young, 2010). The US Environmental Protection Agency estimates that 3% of national energy consumption is used for drinking water and wastewater services, emitting approximately 45 million tons of greenhouse gases into the atmosphere each year (Wallis et al, 2008). The agency is currently working closely with water and power agencies to develop programs that foster more efficient operations (Grumbles, 2008; Strutt et al, 2008).…”
mentioning
confidence: 99%
“…In order for a community to develop effective mitigation and adaptation strategies, local utilities must judge the vulnerability of their infrastructure and operating protocols (Wallis et al 2008). Utilities are encouraged to use risk assessments to account for the uncertainties associated with stormwater and any impacts of changes in climate patterns.…”
Section: Risk Assessments By Utilitiesmentioning
confidence: 99%